(untitled) (African Journal of Biomedical Research, 2020)
Hospital admission is a reflection of prevailing disease pattern in an environment, impact of services rendered in the outpatient department and preventative healthcare services in the community. The aim of this study was to determine the pattern and trend of endocrine related admissions at Ekiti State University Teaching Hospital, Ado-Ekiti. This was a retrospective analysis of health records of patients with endocrine related disorders admitted into the medical wards of the hospital between 2008-2012. The diagnoses, based on WHO ICD-10 were documented. Endocrine related admissions were subdivided into diabetes related, thyroid related and non-diabetes hypoglycaemia. Data of interest were compared with Pearson’s Chi-Square and Student’s t test. There were 3818 admissions out of which 457 (12.0%) were endocrine related. Majority of the endocrine admission were DM related (93.9%), representing 11.8% of the total admissions. There was increase in endocrine-related admissions from 9.1%-18.0% and a 10.6% increase in the DM related admissions from 2008 to 2012, but a decline in absolute number of endocrine admissions notably among females (X2 = 39.88, p<0.001). Poor glucose control (42.8%) was the commonest reason for diabetic admission, followed by hyperglycaemic emergencies (31.1%), diabetic foot disease (15.9%), sepsis (2.6%), stroke (2.3%), nephropathy/renal failure (1.6%), diabetic hand (0.9%), hypoglycaemia (0.9%), heart failure (0.7%). Between 2010-2012, hyperglycaemic crisis emerged as the commonest reason for diabetic admission, but overall, there was significant reduction in the number of hospitalizations for all diabetic complications (X2 = 128.69, df= 36, p=0.000). More resources need to be allocated for the management of diabetes mellitus while efforts to prevent its complications through educational activities and public awareness should be sustained.